PROFILE OF DEATHS IN HOSPITALIZATION FOR SICKLE CELL DISEASE, BRAZIL, 2006-2017 (Movimenta (ISSN 1984-4298), 2021)
Introduction: Sickle cell disease is considered a public health problem in Brazil, because despite advances in health care policies, it remains related to the high prevalence of complications, hospitalizations and low life expectancy. Objective: To describe the profile of deaths in hospitalizations in individuals with sickle cell disease in Brazil. Methods: Descriptive and exploratory study, with secondary data from the reduced hospitalization authorizations (AIH) of the Hospital Information System, Unified Health System (HIS-UHS). The variables analyzed were: sex, age group, race, region, death diagnosis (International Classification of Diseases, ICD-10), federation units and days of hospitalization. The absolute and relative frequencies of the variables were analyzed for all deaths due to sickle cell disorders registered, for three-year period, from 2006 to 2017. Results: Deaths increased in the period studied, with a discreet higher proportion among men, in the age group from 31 to 59 years, black people, concentrating on the Southeast and Northeast regions. The causes of death were recorded as the Sickle disorders, as well as the pulmonary and cardiovascular systems complications, with a hospitalization period of 7 days. Conclusion: Deaths among black young adults related to sickle cell disorders indicate that health policy and programs have advanced in the identification and recognition of the problem, but are still unable to prevent complications and early mortality related to illness.
Keywords: Sickle Cell Anemia; Hospital internment; Mortality; Epidemiology